Magnetic resonance imaging study on temporomandibular joint morphology - Badel, Tomislav (Array, 2009)
Abstract: Magnetic resonance imaging (MRI) has enabled the accomplishment of a more effective diagnostics of temporomandibular disorders (TMD). The sample included 40 patients with clinical symptoms of disc displacement (DD) of temporomandibular joint (TMJ) and 25 subjects included in our study were asymptomatic. DD were diagnosed by clinical examinations which were subsequently confirmed by MRI. DD was found in 18% of the TMJs of the asymptomatic patients. The highest prevalence of total DD without reduction was found in 44.1% of the patients’ joints subsequently followed by total DD with reduction comprising 34.9% of the TMJs and by partial DD with reduction comprising 21% of the TMJs. This study may help us clarify the complicated relationship which exists between the radiographic and clinical findings of TMJ disorders